Enhancing ICJ procedures for litigating in the common interest: the role of third party intervention and amicus curiae briefs / Aprimorando os procedimentos do ICJ para o contribudo do interesse comum: o papel da intervenção de terceiros e as responsabilidades do amicus curiae - Almeida, Paula Wojcikiewicz (Revista de Direito da Cidade, 2019)
Abstract By developing international law, international courts can also contribute to the protection and promotion of community interests, by adjudicating inter-state claims. The aim of this project is, particularly within the International Court of Justice, to appreciate the relentless demands involving community interests and present a non-traditional response to its challenges. The main obstacle faced by the ICJ relates to the existing tension between the bilateral nature of its own proceedings and the multilateral nature of the conflicting substantive law. Whereas the rules of that protect community interests are considered to be substantive law, those guiding international adjudication are of a procedural nature. As procedure may guide and shape the application of substantive law, it should itself be interpreted and developed in a manner to ensure community interests. Our proposal is that using its power to ‘frame rules for carrying out its functions’ (Art. 30 of the Statute of the ICJ), independently from consent, the Court should assume expanded procedural powers in order to ensure the effective application of substantive law whenever community interests are at issue. Most procedural rules can be adjusted and tailored for multiparty aspects (enhancing participatory mechanisms) with the aim of protecting community interests and enhancing international court’s legitimacy. It is up to the Court to find the balance between State’s rights and commonly aspired goals, acknowledging the relation between the emergence of soft international law-making (procedure) and its role of addressing the provision of community interests (substance). Keywords: International Adjudication; Community interests; International Court of Justice; Third party intervention; amicus curiae briefs. Resumo Ao desenvolver o Direito Internacional, os tribunais internacionais também podem contribuir para a proteção e promoção dos interesses da comunidade internacional, ao julgar demandas interestatais. O objetivo deste projeto é, particularmente no âmbito da Corte Internacional de Justiça, apreciar as contínuas demandas envolvendo interesses da comunidade e apresentar uma resposta não tradicional aos seus desafios. O principal obstáculo enfrentado pela CIJ diz respeito à tensão existente entre a natureza bilateral de seus próprios procedimentos e a natureza multilateral da lei substantiva conflitante. Enquanto as regras que protegem os interesses da comunidade internacional são consideradas como uma lei substantiva, as que orientam a adjudicação internacional são de natureza processual. Nossa proposta é que, usando seu poder para “criar regras para o desempenho de suas funções” (Art. 30 do Estatuto da CIJ), independentemente do consentimento estatal, a Corte deveria assumir amplos poderes processuais para assegurar a efetiva aplicação da lei substantiva. sempre que interesses da comunidade internacional estiverem em questão. A maioria das regras processuais pode ser ajustada e adaptada para aspectos multilaterais (reforçando os mecanismos de participação) com o objetivo de proteger os interesses da comunidade e aumentar a legitimidade dos tribunais internacionais. Cabe a Corte encontrar o equilíbrio entre os direitos dos Estados e os objetivos comumente aspirados, reconhecendo a relação entre o surgimento da sua função legisladora - “soft law-making” - (procedimento) e seu papel na promoção dos interesses da comunidade internacional (substância). Palavras-chave: Adjudicação Internacional; interesses da comunidade internacional; Corte Internacional de Justiça; intervenção de terceiros; amicus curiae.